Postprandial lipoprotein metabolism and atherosclerosis. - Karpe, F; Hamsten, A (1995)
The metabolism of chylomicrons and their remnants is a highly facilitated route to distribute energy from the diet for storage in adipose tissue or immediate use in the muscles. It has been proposed that chylomicron remnants are atherogenic, and a delayed clearance of chylomicron remnants seems to be associated with compositional abnormalities of other cholesterol-rich lipoproteins. Furthermore, the plasma concentration of chylomicron remnants is very low compared with all other major lipoprotein species. These arguments suggest that the metabolism of chylomicrons may not be directly implicated in atherogenesis, but it may instead enhance the atherogenicity of endogenous lipoproteins. This review critically examines the current literature in this field.